2012
DOI: 10.5267/j.msl.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Effective factors on mobile phone customer satisfaction

Abstract: Cellular phone is one of the most profitable industries in the world and especially in middle east regions. There is a growing competition among different firms in this market and the market share is exchanged very quickly depending on the features and equipments introduced. Customer satisfaction plays an important role on retaining present marker share or absorbing new customers. In this paper, we present an empirical study to measure the effects of different factors influencing customer satisfaction such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, none of these works has been implemented on East Timor, except for a United Nations' questionnaire on the telecommunications market (UNMIT, 2011). Amongst the studies on that subject, we emphasize the work of Turel and Serenko, 2006;Samuel, 2006;Miranda, 2007;Kang et al, 2009;Bayraktar et al, 2012;Uddin and Akhter, 2012;Mohafez et al, 2012;Asghar et al, 2012;Liu et al, 2013). Mohafez et al (2012) developed a study for Teheran's market, the capital of Iran, in which they found a significant positive connection between perceived expectations and perceived quality and value, being client satisfaction in a position of significance for customer attraction and maintenance.…”
Section: Satisfaction and Service Qualitymentioning
confidence: 95%
See 1 more Smart Citation
“…However, none of these works has been implemented on East Timor, except for a United Nations' questionnaire on the telecommunications market (UNMIT, 2011). Amongst the studies on that subject, we emphasize the work of Turel and Serenko, 2006;Samuel, 2006;Miranda, 2007;Kang et al, 2009;Bayraktar et al, 2012;Uddin and Akhter, 2012;Mohafez et al, 2012;Asghar et al, 2012;Liu et al, 2013). Mohafez et al (2012) developed a study for Teheran's market, the capital of Iran, in which they found a significant positive connection between perceived expectations and perceived quality and value, being client satisfaction in a position of significance for customer attraction and maintenance.…”
Section: Satisfaction and Service Qualitymentioning
confidence: 95%
“…Amongst the studies on that subject, we emphasize the work of Turel and Serenko, 2006;Samuel, 2006;Miranda, 2007;Kang et al, 2009;Bayraktar et al, 2012;Uddin and Akhter, 2012;Mohafez et al, 2012;Asghar et al, 2012;Liu et al, 2013). Mohafez et al (2012) developed a study for Teheran's market, the capital of Iran, in which they found a significant positive connection between perceived expectations and perceived quality and value, being client satisfaction in a position of significance for customer attraction and maintenance. Samuel (2006) suggests to mobile telecommunication companies to maximize their client satisfaction (and therefore improve their businesses' performance), segment the market and adopt specific strategies for different customer segments.…”
Section: Satisfaction and Service Qualitymentioning
confidence: 95%